Characteristics of Mycoplasma pneumoniae infection identified on culture in a pediatric clinic. Issue 2 (11th December 2014) - Katsushima, Yuriko; Katsushima, Fumio; Suzuki, Yu; Seto, Junji; Mizuta, Katsumi; Nishimura, Hidekazu; Matsuzaki, Yoko
Abstract Background The appropriate choice of antibiotics against Mycoplasma pneumoniae infection has become difficult, as the prevalence of macrolide‐resistant M. pneumoniae has increased. Methods Throat swab specimens were collected from children with clinically suspected M. pneumoniae infection while visiting an outpatient clinic. Cultures for M. pneumoniae were done, and all isolates were sequenced for the presence of a mutation in 23S rRNA. Results Of the 80 specimens collected between February 2012 and March 2013, 27 (34%) were positive for M. pneumoniae on culture. Macrolide‐resistant mutation was detected in 24 isolates (89%): 23 isolates had an A2063G transition, and one had a C2617G mutation. Both the median age and the prevalence of pneumonia were significantly higher in M. pneumoniae‐positive than in M. pneumoniae‐negative children (median, 7 years vs 4 years; 88.9% vs 60.4%, respectively). The percentage of serum samples with particle agglutination titer ≥1:160 was 69.6% in M. pneumoniae‐positive cases and 17.6% in M. pneumoniae‐negative cases when the serum was collected ≥4 days after the onset of fever. Defervescence within 72 h after the initiation of macrolides never occurred in M. pneumoniae‐positive children and also did not occur in 54% of M. pneumoniae‐negative children. Switching to either minocycline or tosufloxacin resulted in fever resolution within 48 h in M. pneumoniae‐positive children. Conclusions The described clinical and laboratory characteristics of M. pneumoniae infection may be useful in guiding appropriate treatment in an outpatient clinic.